Financial Distress, Leverage, and Cash Flow Effects on Earnings Management: Evidence from IDX Manufacturing Firms the 2020-2024 Period - Budi Chandra; Erlina Erlina; Parapat Gultom (Harmoni Economics: International Journal of Economics and Accounting, 2025)
Flow on accrual earnings management with firm size as moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This study was conducted based on information obtained from the Indonesia Stock Exchange. The sampling technique used was purposive sampling. The population in this study were manufacturing sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. This study employs panel data regression analysis using E-Views. The analytical method applied is multiple linear regression with a quantitative approach. The findings show that only financial distress has a significant positive effect on accrual earnings management, while the other variables are not significant. In addition, firm size does not moderate the influence of financial distress, leverage, or operating cash flow on accrual earnings management. This research is expected to provide deeper insight into the relationship between financial distress, leverage, and operating cash flow with accrual earnings management, as well as contribute to the accounting literature on earnings management practices amid financial pressure faced by firms.